Pemetaan Jaringan Logistik Daging Sapi di Kotamadya Bandung - Reza Fayaqun; Febriani Sulistiyaningsih (Majalah Ilmiah UNIKOM, 2021)
Beef is a source of animal protein which is still the main choice in meeting the protein needs of some Indonesians. The logistic network mapping problem becomes the main problem in reducing selling prices and meeting the demand for beef in Bandung Municipality. There are three main streams in beef distribution channels, namely material, information and financial flows, where the three streams are interconnected and influence. The flow of material flows from upstream to downstream, namely from butchers to beef consumers. Financial flows flow from downstream to upstream, namely from the final consumer of beef to the butcher. The flow of information flows in the chain reciprocally. The flow of material is divided into two types, namely imported and local beef. Local beef distribution flows from feedlots, local breeders, slaughterhouses, beef wholesalers butchers, retailers to final consumers, namely Horeca, processed industries and household consumers. The components involved in the imported beef logistics network are companies importing beef imported from Australia, New Zealand, Brazil, Spain and India in the form of frozen meat. The financial flow contains the prices from the dealer to the end consumer as well as the payment process. While the flow of information contains beef suppliers, location of purchase, quality of beef and the amount of beef stock in Bandung City. The survey method made beef logistics mapping can be carried out in more detail and clearly. Research on beef logistics route mapping in Bandung certainly very useful for parties involved in beef distribution channel in Bandung. Key Words : beef logistic, inbound logistic, outbound logistic